How Ruins Acquire Aesthetic Value Modern Ruins, Ruin Porn, and the Ruin Tradition - Whitehouse, Tanya (Springer International Publishing, 2018)
This book provides the first recent philosophical account of how ruins acquire aesthetic value. It draws on a variety of sources to explore modern ruins, the ruin tradition, and the phenomenon of "ruin porn." It features an unusual and original combination of philosophical analysis, the author's photography, and reviews of both new and historically influential case studies, including Richard Haag's Gas Works Park, the ruins of Detroit, and remnants of the steel industry of Pennsylvania. Tanya Whitehouse shows how the users of ruins can become architects of a new order, transforming derelict sites into aesthetically significant places we should preserve.